BANYUMAS 1571-1937 (History Department, Semarang State University and Historian Society of Indonesia, 2018)
Banyumas was not a village which grew to become a city, but built directly into a city in the sixteenth century by Adipati (regent) Mrapat. Banyumas as a new center of power was the binary opposition of the toponym Toyareka after its moving from Wirasaba. Back then, Banyumas was inhabited merely by its regents until the beginning of eigthteenth century. The center was then moved again reastward to what it currently known as the old Banyumas and remained there until 1937. The Regent Sudjiman Mertadiredja Gandasubrata then moved the capital of both Banyumas Residency and Regency to Purwokerto, leaving Banyumas - once the biggest city in the residency, just as a capital of a kawedanan or kecamatan (municipality).Â Banyumas bukanlah sebuah desa yang tumbuh menjadi kota, namun dibangun langsung ke sebuah kota pada abad keenam belas oleh Adapati (bupati) Mrapat. Banyumas sebagai pusat kekuatan baru adalah oposisi biner toponim Toyareka setelah pindah dari Wirasaba. Saat itu, Banyumas hanya dihuni oleh bupati sampai awal abad ke-19. Pusat itu kemudian dipindahkan kembali ke tempat yang sekarang dikenal sebagai Banyumas tua dan tetap di sana sampai tahun 1937. Bupati Sudjiman Mertadiredja Gandasubrata kemudian memindahkan ibu kota Karesidenan dan Kabupaten Banyumas ke Purwokerto, meninggalkan Banyumas - yang pernah menjadi kota terbesar di kediaman , sama seperti ibu kota kawedanan atau kecamatan (kotamadya).Â